1976
DOI: 10.1007/bf03006742
|View full text |Cite
|
Sign up to set email alerts
|

Butorphanol tartrate: 2. Safety and efficacy in balanced anaesthesia

Abstract: . AFRICA, FRANK S. CARUSO AND rtOBEltT J. NOVECK BUTOI1PHANOL TAttTRATE has been shown to provide adequate relief of severe post-operative pain for at least four hours when administered to adults intramuscularly in a dose of 2 to 4 rag. Morphine sulphate 10 to 15 mg, meperidine 80 rag/70 kg and pentazocine 30 to 60 mg have a similar effect. 1-4 In normal volunteers, respiratory depression and the suppression of the respiratory stimulating response to carbon dioxide inhalation appears to be less with butorphano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1978
1978
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Many previous studies have shown butor-CANA DIAN ANAESTHETISTS' SOCI ETY JOURNAL phanol tartrate to be a potent analgesic offering excellent pain relief 3-9 and the duration of action in every respect approximates that of morphine sulphate. 3-s, 16 The present study demonstrates that butorphanol tartrate in divided dosesof I to 2 mg is comparable to the intermittent intravenous use of morphine sulphate 5 to 10 mg in a balanced anaesthesia technique with nitrous oxide and oxygen, with a low incidence and severity of side effects and satisfactory amnesia. This conclusion agrees with that of Dobkin,et al,16 who evaluated butorphanol as an analgesic in balanced anaesthesia ;n an open expe0imental design.…”
Section: Discussionsupporting
confidence: 51%
“…Many previous studies have shown butor-CANA DIAN ANAESTHETISTS' SOCI ETY JOURNAL phanol tartrate to be a potent analgesic offering excellent pain relief 3-9 and the duration of action in every respect approximates that of morphine sulphate. 3-s, 16 The present study demonstrates that butorphanol tartrate in divided dosesof I to 2 mg is comparable to the intermittent intravenous use of morphine sulphate 5 to 10 mg in a balanced anaesthesia technique with nitrous oxide and oxygen, with a low incidence and severity of side effects and satisfactory amnesia. This conclusion agrees with that of Dobkin,et al,16 who evaluated butorphanol as an analgesic in balanced anaesthesia ;n an open expe0imental design.…”
Section: Discussionsupporting
confidence: 51%
“…Butorphanol (17‐cyclobutylmethyl‐3,14‐dihydroxymorphinan) tartrate, a member of the phenanthrene class of opioids, is a mixed “agonist‐antagonist” opioid analgesic agent that exerts an analgesic action with a potency seven times greater than that of morphine (Dobkin et al, 1976). Currently, butorphanol tartrate is available for clinical use under the trade name of Stadol.…”
mentioning
confidence: 99%
“…Butorphanol (17‐cyclobutylmethyl‐3,14‐dihydroxymorphinan) is a relatively potent synthetic “agonist‐antagonist” opioid analgesic agent (Pircio et al, 1976; Peachey, 1987) and produces analgesic effects by acting mainly on κ‐opioid receptors (Dobkin et al, 1976; Chang et al, 1983). Several studies have reported that chronic administration of butorphanol results in development of dependence in man (Brown, 1985; Evans et al, 1985) as well as in animals (Pircio et al, 1976; Horan and Ho, 1991).…”
mentioning
confidence: 99%